Subgenome Bias and Temporal Postponement of Gene Expression Contributes to the Distinctions of Fiber Quality in Gossypium Species - Mei, Huan; Qi, Bowen; Han, Zegang; Zhao, Ting; Guo, Menglan; Han, Jin; Zhang, Juncheng; Guan, Xueying; Hu, Yan; Zhang, Tianzhen; Fang, Lei (Frontiers in Plant Science, 2021)
As two cultivated widely allotetraploid cotton species, although Gossypium hirsutum and Gossypium barbadense evolved from the same ancestor, they differ in fiber quality; the molecular mechanism of that difference should be deeply studied. Here, we performed RNA-seq of fiber samples from four G. hirsutum and three G. barbadense cultivars to compare their gene expression patterns on multiple dimensions. We found that 15.90% to 37.96% of differentially-expressed genes showed biased expression toward the A or D subgenome. In particular, interspecific biased expression was exhibited by a total of 330 and 486 gene pairs at 10 DPA and 20 DPA, respectively. Moreover, 6791 genes demonstrated temporal differences in expression, including 346 genes predominantly expressed at 10 DPA in G. hirsutum (TM-1) but postponed to 20 DPA in G. barbadense (Hai7124), and 367 genes predominantly expressed at 20 DPA in TM-1 but postponed to 25 DPA in Hai7124. These postponed genes mainly participated in carbohydrate metabolism, lipid metabolism, plant hormone signal transduction, and starch and sucrose metabolism. In addition, most of the co-expression network and hub genes involved in fiber development showed asymmetric expression between TM-1 and Hai7124, like three hub genes detected at 10 DPA in TM-1 but not until 25 DPA in Hai7124. Our study provides new insights into interspecific expression bias and postponed expression of genes associated with fiber quality, which are mainly tied to asymmetric hub gene network. This work will facilitate further research aimed at understanding the mechanisms underlying cotton fiber improvement.